ANALISIS KESENJANGAN ANTARA JASA YANG DIHARAPKAN DENGAN JASA YANG DITERIMA PADA BENGKEL MOTOR (Studi kasus Bengkel Motor AHASS di Bekasi) - Kumiawati Mulyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2008)
This study discusses the existence of the gap difference between the conformance service with the service perceived by consumers. Usually the service is one factor considered by consumers in product selection decisions. Research methods used in this research is descriptive method because the researcher tries to give an idea about the conditions of service perceived and conformance by consumers. Results showed that the services have been performed by Astra Honda Motor company garage quite well with the average level of consumer satisfaction is 4.09 in the dimension of Tangible, reliability, responsibility, assurance and empathy. However, there is still a little gap between the services perceived by consumers with conformance service.Tthere are differences in average satisfaction level of -0.318 on five dimensions of service quality.